Evaluation of CNS depressant activity of capparis zeylanica lin. root - Mishra S.K.; Singh P.N.; Dubey S.D. (My University, 2025)
The dried ethanolic extract of the root of Capparis zeylanica Lin. (Capparidaceae) was assessed for effect on the Central Nervous System (CNS) using a number of neuropharmacological experimental models in mice. The extract (EECZ) on mice were tested in several animal paradigms, including sodium pentobarbital-induced sleep, open field tests and hole-cross tests. Mice acutely treated with ethanolic extract of Capparis zeylanica (EECZ) at 100, 200 and 400 mg kg-1 doses prolonged the sleeping time induced by pentobarbitone (40 mg kg-1). This extract, at 100 and 200 mg kg-1 doses, showed a sedative effect in the hole-cross paradigm and decreased spontaneous activity in mice. The EECZ treatment did not produced mortality up to 2000 mg kg-1. Chemical analysis showed that the EECZ alkaloids, steroids, phytosterol, fatty acids, phenols, flavonoids, flavonols, tannins and mucilage are the main compounds of the active extract. The extract produced a dose-dependent reduction of the onset and duration of pentobarbitone induced hypnosis, reduction of locomotor and exploratory activities in the open field, hole-cross tests etc. At the same dose levels, the ethanolic extract of Capparis zeylanica (EECZ) root dose-dependently inhibited acetic acid-induced writhing in mice. The mechanism of this depression is not clearly understood at this point but it can be assumed that the drug may exert CNS depressant effect by interfering with the function of cortex. The results have suggested that the crude hydroalcholic extract of Capparis zeylanica root possesses some biologically active constituents with sedative activities. © 2011 Academic Journals Inc.